2014
DOI: 10.1007/s10393-014-0917-z
|View full text |Cite
|
Sign up to set email alerts
|

Invasive American Mink: Linking Pathogen Risk Between Domestic and Endangered Carnivores

Abstract: Infectious diseases, in particular canine distemper virus (CDV), are an important threat to the viability of wild carnivore populations. CDV is thought to be transmitted by direct contact between individuals; therefore, the study of species interactions plays a pivotal role in understanding CDV transmission dynamics. However, CDV often appears to move between populations that are ecologically isolated, possibly through bridge hosts that interact with both species. This study investigated how an introduced spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 68 publications
1
22
0
7
Order By: Relevance
“…The habitats of these species are native temperate forest (guigna, Darwin's fox, pudu) and riparian habitats (river otter). Species presence in these habitats in this particular study area had been confirmed by previous A c c e p t e d M a n u s c r i p t and continuing studies using camera traps and interviews (Farías et al, 2014;Sepúlveda et al, 2014a;Sepúlveda et al, 2014b;Silva-Rodríguez and Sieving, 2012).…”
Section: Habitat Classification and Analysis Of Dog Habitat Use And Fsupporting
confidence: 70%
See 1 more Smart Citation
“…The habitats of these species are native temperate forest (guigna, Darwin's fox, pudu) and riparian habitats (river otter). Species presence in these habitats in this particular study area had been confirmed by previous A c c e p t e d M a n u s c r i p t and continuing studies using camera traps and interviews (Farías et al, 2014;Sepúlveda et al, 2014a;Sepúlveda et al, 2014b;Silva-Rodríguez and Sieving, 2012).…”
Section: Habitat Classification and Analysis Of Dog Habitat Use And Fsupporting
confidence: 70%
“…These include (but are not limited to) 'stray' dogs and owned farm and pastoral companion dogs whose daily activity pattern may involve ranging that can bring them into contact with wildlife, especially when human habitations border wildlife reserves or other natural areas'. In this area, dogs represent an important threat for the conservation of endangered species such as the southern pudu (Pudu puda) (Endangered, IUCN, 2014) by predation (Silva-Rodríguez and Sieving, 2012), Southern river otters (Lontra provocax) (Endangered, IUCN, 2014) by disease transmission (Sepúlveda et al, 2014b) and interspecific killing (Espinosa, 2012), and the Darwin fox (Lycalopex fulvipes) (Critically Endangered, IUCN, 2014) by interspecific killing and disease transmission (Farías et al, 2014). We conducted our study in Cadillal Alto, a small human settlement that includes 11 families/households located on the north bank of M a n u s c r i p t the Chaihuín River between two protected areas, the Valdivian Coastal Reserve (VCR) and the Alerce Costero National Park (ACNP) (Fig.…”
Section: Study Areamentioning
confidence: 99%
“…American mink may also serve as a reservoir and involve in circulation of Trichinella in nature. It is killed and eaten by most of larger than mink predators, including wolves (Canis lupus), bobcats (Lynx rufus), Eurasian lynx (Lynx lynx), otters (Lutra lutra), red fox (Vulpes vulpes) and arctic fox (Vulpes lagopus) as well as by dogs (Canis lupus familiaris) (Errington, 1937;Hamilton and Hunter, 1939;Grigorev and Egorov, 1969;Hersteinsson and Macdonald, 1996;Bryan et al, 2006;Odden et al, 2006;Sepúlveda et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Por ejemplo, la introducción de especies alóctonas que porten un patógeno desconocido para especies nativas puede signifi car la aparición de enfermedades emergentes (Medina-Vogel 2010, Deem et al 2001 Sepúlveda et al 2014). Por otra parte, la introducción de patógenos en nuevas áreas geográfi cas puede ocurrir como consecuencia de planes de manejo que incluyan la translocación de animales (Deem et al 2001), situación que representa una seria amenaza para los programas de conservación (Cunningham 1996).…”
Section: Discussionunclassified